Amorfrutin A inhibits TNF-α induced JAK/STAT signaling, cell survival and proliferation of human cancer cells. (2nd November 2017) - Mi, Chunliu; Ma, Juan; Wang, Ke Si; Wang, Zhe; Li, Ming Yue; Li, Jun Bo; Li, Xuezheng; Piao, Lian Xun; Xu, Guang Hua; Jin, Xuejun
Abstract: Context: Amorfrutin A is a natural product isolated from the fruits of Amorpha fruticosa L. and has been shown to exhibit multiple bioeffector functions. In the present study, we investigated whether amorfrutin A exerts anticancer effects by inhibiting STAT3 activation in cervical cancer cells. Objective: To investigate the effectiveness of amorfrutin A as a treatment of cancer, and determine the underlying pharmacological mechanism of action. Materials and methods: HeLa, SK-Hep1, MDA-MB-231 and HCT116 cells were used in this study. Major assays were luciferase reporter assay, MTT, Western blot analysis, immunofluorescence assay, reverse transcription-PCR (RT-PCR), flow cytometric analysis, EdU labeling and immunofluorescence, xenografted assay. Results: Amorfrutin A significantly inhibited tumor necrosis factor-α (TNF-α)-induced phosphorylation and nuclear translocation of STAT3 in human cervical carcinoma cells. Amorfrutin A also inhibited activation of the upstream kinases Janus-activated kinase 1 (JAK1), JAK2 and Src signaling pathways. Furthermore, amorfrutin A increased the expression of p53, p21, p27, induced cell cycle arrest in the G1 phase as well as decreased levels of various oncogene protein products. In vivo studies further confirmed the inhibitory effect of amorfrutin A on the expression of STAT3 proteins, leading to a decrease growth of HeLa cells in a xenograft tumor model. Discussion and conclusions: The results indicated that amorfrutin A is a potent inhibitor of STAT3 and provide new perspectives into the mechanism of its anticancer activity.